Cathy Freeman, reconciliation and the burden of history. Issue 3 (4th May 2022) - Nolan, Maggie
ABSTRACT: On 25 September 2020, the ABC released a documentary film to mark the twentieth anniversary of Cathy Freeman's gold medal victory in the women's 400 metres at the 2000 Sydney Olympics. Media interest in Freeman's victory still erupts periodically, most recently, to commemorate the twentieth anniversary. This article revisits Cathy Freeman's historic gold-medal-winning performance in order to ponder the lost promise of reconciliation. At the time, and still today, Freeman's victory is overwhelmingly celebrated as more than just an athletic feat; it is also lauded as a victory for reconciliation. Rather than trying to determine the extent to which Freeman's race did bolster reconciliation, or even whether it contributed to reconciliation at all, this article instead analyses the metaphors, rhetoric and images through which Freeman's victory was represented as an act of reconciliation, and what this tells us about how reconciliation plays out in the Australian context. In particular, it argues that the complex ways in which Freeman's victory were represented, and continue to be understood, reveal a widespread desire to be free from the burdens of history by projecting the work of reconciliation onto Freeman herself.